Análisis de la política de créditos de la Caja Municipal de Ahorro y Crédito de Trujillo y su incidencia en los niveles de morosidad de los microempresarios fabricantes del sector calzado en el distrito El Porvenir - período 2014 - 2015 - Segura Sánchez, Luis Antonio (2017)
This research is made in order to analyze the credit policy of the Caja Trujillo and its impact on delinquency levels microentrepreneurs manufacturers of the footwear sector in the period- 2014-2015. For this report the non-experimental research transactional correlational / causal design as well as the following methods were used: inductive and hypothetical method; and finally the following research techniques were applied: surveys and observation, which was surveyed a sample of 188 microenterpreus It was concluded that the policy of expanding credit, by increasing the growth rate of placements, causes the levels of requirement and control relax and therefore begin to lend to individuals with a default probability more higher than the bank . That's why preventive measures must be taken as risk diversification, constant advisers as they are applied by Caja Trujillo training to successfully meet these threats.